Productivity and nutritive value of Tifton 85 bermudagrass inoculated with Azospirillum brasilense in association with nitrogen fertilization - Rodrigues Silva, Aline; Jorge Olivo, Clair; Martins Granada, Diego; Casagrande, Lucas Giovane; Pase Quatrin, Mauricio; Paim Sauter, Caroline (Revista Ceres, 2023)
Tifton 85 bermudagrass has been widely used in tropical and subtropical regions. Owing to its high forage yield, the fertilizer requirement of Tifton 85 is also high. Inoculation with Azospirillum brasilense is an alternative to reduce the use of nitrogen fertilizers and decrease their environmental impact. However, the effects of inoculation in tropical grasses remain poorly understood. This study aimed to evaluate the productivity, pasture characteristics, and nutritive value of Tifton 85 bermudagrass inoculated with A. brasilense in association with nitrogen fertilization. The study evaluated four nitrogen levels (0, 100, 200, and 300 kg ha−1), inoculated and uninoculated, under cutting conditions. The experimental design was completely randomized, in a factorial arrangement, with two qualitative (inoculated with A. brasilense or uninoculated) and four quantitative levels (nitrogen doses) with three replications (24 plots). Botanical composition and morphological characteristics, leaf blade/stem+sheath ratio, nutritive value, and forage yield were evaluated. The inoculation increased the leaf blade/stem+sheath ratio and forage yield of Tifton 85, but did not affect crude protein concentration, neutral detergent fiber content, and total digestible nutrient content of the forage constituted by Tifton 85 leaf blades. The protein concentration and forage production corresponded linearly to the nitrogen dose increase.